2000
DOI: 10.1073/pnas.100588797
|View full text |Cite
|
Sign up to set email alerts
|

A functional R domain from cystic fibrosis transmembrane conductance regulator is predominantly unstructured in solution

Abstract: Phosphorylation of the regulatory (R) domain initiates cystic fibrosis transmembrane conductance regulator (CFTR) Cl ؊ channel activity. To discover how the function of this domain is determined by its structure, we produced an R domain protein (R8) that spanned residues 708 -831 of CFTR. Phosphorylated, but not unphosphorylated, R8 stimulated activity of CFTR channels lacking this domain, indicating that R8 is functional. Unexpectedly, this functional R8 was predominantly random coil, as revealed by CD and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
117
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 51 publications
9
117
0
Order By: Relevance
“…Previously, circular dichroism spectra of the isolated R domain revealed that it was mostly unstructured and that phosphorylation didn't have any effect on its secondary structure (11). But the conformation of the entire protein was not yet examined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, circular dichroism spectra of the isolated R domain revealed that it was mostly unstructured and that phosphorylation didn't have any effect on its secondary structure (11). But the conformation of the entire protein was not yet examined.…”
Section: Discussionmentioning
confidence: 99%
“…PKA phosphorylation relieves this inhibition. On the other hand, it has been shown that exogenous phosphorylated R domain (either residues 590 -858, 645-834, or 708 -831) increases the open probability of a CFTR channel construct missing residues 708 -835 from the R domain (7,10,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another likely possibility is that the deletion of the F508 residue affects the interaction of the R domain with other regions of CFTR. The R domain is thought to be largely disordered (Ostedgaard et al, 2000), but it contains ordered segments of helical structure (Baker et al, 2007), and it has been shown to interact directly with both the NBD1 domain (Baker et al, 2007), and with the N-terminal tail of CFTR (Naren et al, 1999). Translation of the R-domain is also important in ensuring that N-terminal regions of CFTR achieve a compact folded structure that can no longer be recognized by the Hsp40 Hdj-2 (Meacham et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…One model to explain this mode of regulation involves the binding of multiple phosphorylation sites, potentially with different affinities and effects, to multiple CFTRbinding surfaces, so that increased phosphorylation leads to increased channel activity 3 . Understanding the dynamic, multisite interactions involved in this model at the molecular level requires specific consideration of the R region as an intrinsically disordered protein segment.…”
mentioning
confidence: 99%